2012
DOI: 10.1007/s00384-012-1501-z
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of colorectal cancer enhances access to multimodal therapy and compliance with National Comprehensive Cancer Network (NCCN) guidelines

Abstract: Multidisciplinary clinic management of colorectal cancer is associated with a significantly more complete preoperative evaluation as well as improved access to multimodal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…All studies concluded that a multidisciplinary setting resulted in improved patient outcomes in terms of diagnosis and/or treatment planning [14][15][16][18][19][20][21][22][25][26][27][28][29][31][32][33][35][36][37]40,42], improvements in survival [15,17,21,23,[28][29][30]36,39,41], patient satisfaction [24,31,38] and clinician satisfaction as a consequence of teamwork communication and cooperation [15,34]. Evidence of improved survival was found for colorectal [15,17,28,36], head and neck [29,41], breast [39], oesophageal [21] and lung [30] cancer.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies concluded that a multidisciplinary setting resulted in improved patient outcomes in terms of diagnosis and/or treatment planning [14][15][16][18][19][20][21][22][25][26][27][28][29][31][32][33][35][36][37]40,42], improvements in survival [15,17,21,23,[28][29][30]36,39,41], patient satisfaction [24,31,38] and clinician satisfaction as a consequence of teamwork communication and cooperation [15,34]. Evidence of improved survival was found for colorectal [15,17,28,36], head and neck [29,41], breast [39], oesophageal [21] and lung [30] cancer.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
“…The studies documented two motivating principles: firstly, MDTs ensure more appropriate treatment through a preoperative review of imaging and pathology results [19,20,22,25,26,40,42]; and secondly, a multidisciplinary approach guarantees the most up-todate treatment for all cancer patients seen at the facility or discussed online [16,18,21,23,32,33,35,[38][39][40][41]53]. Other clinical-based goals included improving patients' quality of life [24,32,42,[53][54][55] and setting up a structured followup care plan [53,[59][60][61].…”
Section: Mdt Goals and Scope Of Practicementioning
confidence: 99%
See 3 more Smart Citations